The talitrid amphipod genus Talorchestia from the South China Sea to the Indonesian Archipelago (Crustacea, Senticaudata) - Lowry, J.k.; Springthorpe, R.t.; Azman, B.a.r. (Zootaxa, 2017)
We redescribe Talorchestia gracilis (Dana, 1852a) for the first time and designate a neotype based on new collections from Pulau Layang-Layang, Swallow Reef, South China Sea. We describe T. bunaken sp. nov. from Bunaken Island, Northern Sulawesi, Indonesia, T. dili sp. nov. from Dili, Timor-Leste, T. seringat sp. nov. from Singapore, T. sipadan sp. nov. from Sipadan Island, Sabah, Malaysia and T. yoyoae sp. nov. from Lombok, Indonesia. We report T. spinipalma (Dana, 1852a) from Madang, northern Papua New Guinea.